EVALUASI PENERAPAN TOTAL PRODUCTIVE MAINTENANCE PADA LINI PRODUKSI PACKHOUSE DI PT XWZ, Tbk- NAROGONG PLANT - Doni Yusri; Chairul Anwar (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2022)
PT XWZ is a manufacturing company that produces several types of cement. The maintenance of the production performance by employees at this company is important due to increasing productivity meet. If the production process runs according to the planned schedule, it will produce quality products, the right time to complete the production process, and low production costs. The implementation of Total Productive Maintenance (TPM) is one of solutions to improve production performance by involving the company's human resources for maintaining in production including the management of equipment and machine maintenance. There are several aims in this study aims, namely evaluating the implementation of TPM, evaluating the facility maintenance management system, identifying the implementation of the 8 pillars of TPM, analyzing the application of 5S culture, and analyzing the F-Tags Category. The results showed that TPM activities, facility maintenance, implementation of the 8 pillars, 5S culture had been carried out well. ABSTRAKPT XWZ, Tbk merupakan perusahaan manufaktur yang memproduksi semen. Perawatan peralatan dan mesin oleh karyawan di lini produksi pada perusahaan menjadi penting dikarenakan tuntukan produktivitas yang semakin tinggi. Proses produksi yang berjalan sesuai dengan jadwal yang telah direncanakan, akan mempengaruhi kualitas produk yang dihasilkan, waktu penyelesaian proses produksi yang tepat, serta biaya produksi yang murah. Penerapan Total Productive Maintenance (TPM) merupakan salah satu cara untuk meningkatkan kinerja produksi dengan melibatkan sumberdaya manusia yang dimiliki perusahaan terhadap perawatan lini produksi termasuk mesin packhouse. Penelitian ini bertujuan untuk mengkaji penerapan TPM, mengevaluasi sistem manajemen perawatan fasilitas, mengevaluasi pelaksanaan 8 pilar TPM, mengidentifikasi pelaksanaan budaya 5S, dan menganalisis F-Tags Category. Hasil penelitian menunjukan bahwa kegiatan TPM, perawatan fasilitas, pelaksanaan 8 pilar, budaya 5S telah dilakukan dengan baik namun belum maksimal.